Lands of majesty the Americas - Goeckel, Brendan; Markus, Lorraine; Williams, Jason (Great national parks of the world, 2000)
Travel the Americas to explore four of the world's most beautiful National Parks. Cruise the icy waters of Alaska's glittering Glacier Bay and se whales breaching, eagles soaring, glaciers thundering into the sea! Wander through lush green Corcovado, Costa Rica's enchanting rainforest, amidgorgeous scarlet macaws and spider monkeys. Journey to Canada's majestic Banff National Park to enjoy brilliant turquioise Lake Louise nestled beneath the soaring Rockies. Behold Arizona's awe-inspiring Grand Canyon - so magnificent it's been called "an amphitheatre fit for the gods!"